Teaching English in Nepal and its Space in Secondary Level Curriculum - Timsina, Jib Nath (Tribhuvan University Journal, 2023)
This paper analyzes Nepali Secondary Level Curriculum to identify the spaces of English from 1990 BS to 2079 using descriptive approach. The information was collected using observation check list with the weekly/annual weight age, full marks and credit hours of English. The findings reveal that there ions systematic way of inclusion of English with its weight age and full marks which is found gradually decreasing as compared to the past. The study also shows the space of English was strong at the beginning of the curriculum (1990 BS) till 2028BS in which 200 marks for compulsory English papers were included in the SLC (Secondary) curriculum. The weight age of English is being reduced from 12, 7, 5, 4 period weight age weekly. Currently, the secondary curriculum incorporates agrading system and credit hours since 2016 in SEE. In grade 9-10, students are required to complete 160 annual hours of compulsory English, which carries a weight of 5 credit hours. Additionally, students have the option to take 128 annual working hours of optional English, which carries a weight of 4 credit hours. In grades 11 and 12, compulsory English carries a weight of four credit hours and requires 128 annual working hours, which is comparatively lower than other subjects. However, general subjects such as Shanskrit, Gonpa, and Madarsha offer optional English, which consists of five credit hours and 160 annual working hours.